The Effectiveness of Omar and Hana's Video Based Learning in Fostering Students' Religious Character - Rahmat Kurniawan; Zuhdiah; Rina Marliana (Passikola: Jurnal Pendidikan Dasar & Madrasah Ibtidaiyah, 2025)
This study aims to determine the effectiveness of Video Based Learning of Omar and Hana's animated films in fostering students' religious characters. This research is a quantitative research with a pre-experimental approach  using a one group pretest-posttest design. The research population is grade IV students of SD Negeri 20 Rangas with a total of 37 students. The sampling technique used purposive sampling with a sample of 21 students. The data collection method was carried out through questionnaires. The data analysis technique used descriptive and inferential statistics with normality tests, and t-tests using paired sample t-test. Based on the results of the study, it was found that the religious character of students before the application of the Video Based Learning method  was in the category of sufficient with an average pre-test score  of 55.00. The religious character of students after the application of the Video Based Learning method  increased to a good category with an average post-test score  of 69.76. (3) There is a significant growth between Video Based Learning and the growth of students' religious character, as evidenced by the results of the t-test showing a significance value of 0.000 (<0.05), so that H1 is accepted and H0 is rejected. Thus, this method has proven to be effective in fostering the religious character of students.